Mental health in elite coaches - Baumann, L.; Schneeberger, A. R.; Currie, A.; Iff, S.; Seifritz, E.; Claussen, M. C. (Sports Health: A Multidisciplinary Approach, 2024)
Context: Coaches play an important role in promoting mental health in elite sports. However, they themselves are exposed to risks affecting their mental health, and their fears and worries are often overlooked. Moreover, it remains unclear how coaches` mental health affects their athletes` mental health.